2002
DOI: 10.1116/1.1532738
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of clean InP(100) surfaces studied by synchrotron radiation photoemission

Abstract: Wet chemical cleaning of InP surfaces investigated by in situ and ex situ infrared spectroscopyDependence of indium-tin-oxide work function on surface cleaning method as studied by ultraviolet and x-ray photoemission spectroscopiesThe chemical cleaning of indium phosphide ͑InP͒,͑100͒ surfaces is studied systematically by using photoemission electron spectroscopy. In order to achieve the necessary surface sensitivity and spectral resolution, synchrotron radiation with photon energies ranging from 60 to 600 eV a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 22 publications
2
30
0
Order By: Relevance
“…The one on the left with kinetic energy 1.35 ± 0.05eV lower than bulk peak (i.e. higher binding energy) is assigned as elemental Phosphorous in our early study [14], with coverage of about 0. At the beginning of the reaction, H atoms bind to the surface phosphorous atoms, so the surface will have a hydrogen termination on the phosphorous sites after treatment with a strong acid solution.…”
Section: Methodsmentioning
confidence: 71%
“…The one on the left with kinetic energy 1.35 ± 0.05eV lower than bulk peak (i.e. higher binding energy) is assigned as elemental Phosphorous in our early study [14], with coverage of about 0. At the beginning of the reaction, H atoms bind to the surface phosphorous atoms, so the surface will have a hydrogen termination on the phosphorous sites after treatment with a strong acid solution.…”
Section: Methodsmentioning
confidence: 71%
“…For the S-passivated sample, the In-S/O concentration is very small and does not change significantly after ALD at different temperatures. Figure 2 shows the P 2p spectra from the (a) native oxide, (b) acid etched, (c) S-passivated samples, before ALD, and after 10 cycles of HfO 2 ALD at 200 C, 250 C and 300 C. The peak with a binding energy separation of þ4.0 eV to the InP bulk peak is assigned to P-OH bonding; 24 the peak with a binding energy separation of þ4.5 eV to the InP bulk peak is assigned to InPO 4 , and the peak with a binding energy separation of þ5.1 eV is assigned to In(PO 3 ) 3 . 19,23 Figure 2(d) shows the ratio of the total P-oxide peak area to that of the InP bulk peak of each respective surface.…”
Section: Methodsmentioning
confidence: 99%
“…This study looks at the ''half cycle'' interaction between atomic-layer deposited (ALD) aluminum oxide (Al 2 O 3 ) film growth on (NH 4 ) 2 S treated and acid etched InP surfaces to determine the resultant interfacial chemistry between the trimethyl aluminum (TMA) ALD precursor and the substrate to investigate whether the reported oxide ''clean up'' effect seen on GaAs and InGaAs surfaces also takes place for InP. [12][13][14] Sulfur-doped n-type InP (100) 15) a sample treated with ammonium sulfide in 10% (NH 4 ) 2 S in H 2 O for 20 min at room temperature, 16,17) and a sample subjected to a combination of two-stage etching followed by the same ammonium sulfide treatment. The samples were then rinsed in flowing deionized (DI) water for 10 s, blown dry in N 2 and inserted into an ultrahigh vacuum (UHV) system within 7 min.…”
mentioning
confidence: 99%
“…15) Prior computational modelling of amorphous 24) and crystalline 25) InP has suggested that P-P and dangling bond species, if present, can lead to deleterious gap states. However, further work in modelling high-k/InP interfaces is needed to establish the correlation of the chemical states observed and potential gap states.…”
mentioning
confidence: 99%